Impact of Guidewire Caliber on ERCP Outcomes: Systematic Review and Meta-Analysis Comparing 0.025- and 0.035-Inch Guidewires - Aziz, Muhammad (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.